Lūthāng kānlongthun tām ph̄æn yutthasāt kānphatthanā Čhangwat Chīang Mai : sarup samrap phūb̨ōrihān (Samnakngān Čhangwat Chīang Mai, 2005)
Executive summary of the economic development plans and strategies for Chiang Mai province, Northern Thailand.